Exploring family dynamics: A confirmatory factor analysis of family functioning in Thai family-owned businesses - Apisakkul, Akachai; Chirapanda, Suthawan (Asian Economic and Financial Review, 2025)
This study aims to develop a comprehensive model of family functioning specifically tailored to family-owned businesses in Thailand and to assess its alignment with empirical data, focusing on key components that influence the sustainability and performance of such businesses. Data were collected from 305 family members involved in family-owned businesses using a family functioning assessment. Confirmatory Factor Analysis (CFA) was conducted using AMOS software to evaluate the model's fit with the empirical data. The analysis identified five critical components of family functioning: Problem Solving, Communication, Roles, Affective Responsiveness, and Affective Involvement. The model showed excellent alignment with empirical data, yielding favorable fit indices (χ² = 18.956, df = 14, RMSEA = 0.034, CFI = 0.998), confirming the proposed hypotheses. The study confirmed that effective family functioning—characterized by open communication, clear role definitions, and emotional bonds—is essential for the cohesion and long-term success of family-owned businesses in Thailand. The model provides valuable insights into how family dynamics influence business outcomes and intergenerational collaboration. Emphasizing communication, structured problem-solving, and role clarity can enhance operational efficiency, reduce conflicts, and strengthen succession planning, ensuring the sustainability of family businesses in a changing economic environment.